Moin, Schietwedder, and Freely Phrased Sentences: The Commodified Use of Low German on Instagram - Schram Frederike (Germany, 2025)
In the context of a generally heightened awareness of regional or minority languages, new domains of usage, and the increased prestige of Low German, this article focuses on the use of Low German in the captions of commercial Instagram posts. By employing a mixed-methods approach of qualitative and quantitative data analysis, the captions are analysed based on language choice, distribution, and usage. Questions are addressed as to how commercial Instagrammers employ Low German for marketing, what kind of texts, linguistic structures, and lexical items are employed, and in which linguistic context Low German is used. The findings show that commercial Instagrammers primarily embed a small set of commonly known Low German words into High German sentences. In this way, they establish a connection between a shared, distinct Northern German identity, their products, and themselves. With this conscious usage of the regional language Low German, the promoted products and the commercial Instagrammers thus stand out from comparable others in a competitive global market.